LIABILITY OF INTERNET INTERMEDIARIES FOR COPYRIGHT INFRINGEMENT - Trotsyuk, Nina V.; Kudzinovskiy, Artem S. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article researches the concept and types of Internet intermediaries. The peculiarities of the responsibility of these subjects in accordance with national and international legislation are determined.